Hyaluronic acid filler injection for upper body aesthetic contouring - Yi, Kyu-Ho; Wan, Jovian; Yoon, Song Eun; Basmage, Lucas; Bautzer, Carlos (JPRAS open, 2025)
The demand for non-surgical upper body enhancement continues to grow, particularly among men seeking improved muscular definition without the risks of surgery or functional compromise. This case report presents a novel protocol using high G-prime hyaluronic acid (HA) fillers (Sedifill; Maypharm, Seoul, Republic of Korea) to contour the pectoralis major, deltoid, biceps, and brachioradialis in a 41-year-old male with moderate subcutaneous adiposity (BMI: 25 kg/m²; body fat: 21 %). A total of 134 mL of filler was injected subcutaneously using a layered technique with dynamic assessment and feathering to enhance muscle visibility while integrating with surrounding fat. Immediate improvements were noted in chest lift, deltoid rounding, and arm tapering, with no complications at one-month follow-up. The patient reported high satisfaction and increased confidence in appearance. This approach demonstrates the feasibility and adaptability of HA filler contouring in individuals with higher body fat, highlighting the importance of customized protocols to overcome adipose masking and achieve natural, balanced results. While not a substitute for fat reduction, this technique offers a safe, reversible alternative for patients seeking aesthetic enhancement and may serve as a motivational catalyst for healthier lifestyle changes. Further studies are needed to assess long-term outcomes and validate efficacy across broader populations.